Interventricular Septal Hematoma and Coronary-Ventricular Fistula: A Complication of Retrograde Chronic Total Occlusion Intervention - Abdul-rahman R. Abdel-karim; Minh Vo; Michael L. Main; J. Aaron Grantham (Case Reports in Cardiology)
Interventricular septal hematoma is a rare complication of retrograde chronic total occlusion (CTO) percutaneous coronary interventions (PCI) with a typically benign course. Here we report two cases of interventricular septal hematoma and coronary-cameral fistula development after right coronary artery (RCA) CTO-PCI using a retrograde approach. Both were complicated by development of ST-segment elevation and chest pain. One case was managed actively and the other conservatively, both with a favorable outcome.